Review of Scholarship on the Admonitions of King Saint Stephen of Hungary - Nemerkényi, Előd (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The purpose of the following discussion is to demonstrate that the philological study of the fortuna of the Admonitions of King Saint Stephen of Hungary provides important contributions to the characteristic stages of the development of Latinist scholarship from the Middle Ages and the Renaissance until today. The Admonitions, a mirror of princes composed in the eleventh century and attributed to the first Christian king of Hungary, has attracted pious and scholarly attention for a millennium – including the hagiographic tradition of medieval Hungary and the legal tradition of the Corpus iuris Hungarici. Based on its late manuscript tradition, hypercritical scholars suggested that the Admonitions was a humanist forgery or at least an interpolated and stylistically polished text. From the Renaissance on, philologists and editors have addressed various issues of textual criticism such as the problem of dating and authorship, grammatical features (orthography, morphology, and syntax), stylistic devices (vocabulary, prose rhyme and rhythm), and textual parallels (Biblical, Classical, and Carolingian Latin). The way scholars have studied the Latinity of the Admonitions against the standards of Classical, Medieval, and Humanistic Latin for centuries reveals a great deal about their own approaches to their Latinist trade in particular – and therefore about Neo-Latin studies in general.